Charlotte's web - White, E. B. (Elwyn Brooks), 1899-; Williams, Garth (New York, N.Y. : Harper, 2012)
Wilbur the pig is desolate when he discovers that he is destined to be the farmer's Christmas dinner - then his spider friend, Charlotte, decides to help him.
Newbery Honor Book, 1953.
Keywords: Pigs -- Juvenile fiction; Spiders -- Juvenile fiction; Friendship -- Juvenile fiction; Domestic animals -- Juvenile fiction; Farm life -- Juvenile fiction